Outcomes for circulatory death and brainstem death pancreas transplantation with or without use of normothermic regional perfusion. Issue 12 (22nd June 2021) - Richards, J A; Roberts, J L; Fedotovs, A; Paul, S; Cottee, S; Defries, G; Watson, C J E; Pettigrew, G J
Abstract : Simultaneous pancreas and kidney transplantation is the optimum treatment for patients with type 1 diabetes and renal failure, providing survival benefit over deceased donor kidney transplant alone. Here the authors demonstrate that utilization of donation after circulatory death pancreases is a safe approach to expanding the donor pool with equivalent results to donation after brainstem death transplantation. They also demonstrate that pancreas transplantation after normothermic regional perfusion is feasible, but it will require ongoing prospective study to ensure that the benefits seen for liver transplantation do not come at the expense of pancreas transplant outcomes.